Conflict Coaching: Conflict Management Strategies and Skills fot The Individual - Tricia S. Jones, Ross Brinkert (Sage, 2008)
Conflict Coaching: Conflict Management Strategies and Skills for the Individual defines this growing area of conflict resolution and distinguishes conflict coaching as a stand-alone resolution technique. In a service society where human relationships are central to our professional as well as personal lives, individuals value one-on-one attention to obtain custom solutions for handling important interpersonal communication. The CD-ROM accompanying the book provides numerous resources for instructors, coaches, and other interested readers.